Rainbows of Multiple Orders - Holovatsky, Volodymyr (Wolfram, 2022)
This Demonstration shows the position and colors for the first 10 orders of rainbows formed by the reflection and refraction of the Sun's rays in drops of water.
Keywords: Rainbows of Multiple Orders